Disputed names: Analysis of naming strategies used by politicians in Peruvian media during the coverage of two corruption cases - Arrunátegui, Carolina (2021)
This article analyzes the naming strategies used by politicians in the Peruvian media during the coverage of two corruption cases in which the reputation of two presidents of the Republic was at stake. Based on the work of Theodoor van Leeuwen (1996), we call naming strategies the various ways in which politicians named people and facts in order to control meanings and build versions according to their interests. As an analytical tool, we have used Van Leeuwen’s (1996) model of Representation of Social Actors, from the perspective of Critical Analysis of Discourse, which understands language as a socially and historically situated practice (Fairclough, 1992 and 2003). The results of the analysis show that names can be powerful political weapons; in this sense, it should be understood that naming practices are not merely an exercise in linguistic labeling, but social practices that construct reality, since naming is also creating what is named.